دراسة عن مصطلحات الإمام مالك في الموطأ: A study on the terminology of Imam Malik in Al-Muwatta - Dr. Maroof Heravi (MEI, 2023)
There is no doubt that al-Muwatta is the most authentic book after the two Sahihs (Bukhari and Muslim), and it is one of the first books that appeared in its chapter, especially in its selection of authentic hadiths, in addition to the jurisprudence of its author and his position in hadith, and his reputation among the modernists. Scholars of his time, and those after them to this day, have attested to his knowledge in jurisprudence and hadith. Imam Malik was keen to mention the correct one without others, but it has some terminology that contradicts the condition of validity, and the hadith scholars have criticized it through these terms, and we have clarified most of these terms in this article, including: (mostalah al-balaghat)The term communications: Malik has been more likely to mention the word "inform me" and "inform us", which is known as "communications", and it appears that these communications have lost a condition of health, namely, the connection of the bond, and therefore should not be confirmed, but the origin is weak because of the interruption of attribution, but it is different from the communications in the position because the most of them are fixed. Another terminology is Malik’s saying: “The Sunnah in which there is no difference in us is such and such.” It appears from the apparent meaning of this term that there is consensus, or at least the absence of disagreement in the matter, and this is not the case. Rather, Imam Malik expresses with this term the sayings of the seven jurists, and the scholars of Medina. Another terminology is Malik’s saying: “This is the best that I have heard.” That is, if the scholars of Medina differed, he took the strongest and most correct of their sayings according to what appeared to him, either by the many who said it, or by the agreement of a strong analogy. Another terminology is Malik's saying "on trust “or "trustworthy narrator "without mentioning his name, description, lineage, or any other matter that indicates it. This terminology has been used in several hadiths from his book, and after investigation and study, we found that these narrators are trustworthy, as Imam Malik said. Another terminology is Malik’s saying: “Tell me who among the people of knowledge I am not accused of,” and his saying, “On this I have found the people of knowledge in our country,” or “The matter is with us.” He means Rabi’a and Ibn Hormuz. Jurisprudence and science did not differ in it, and if he says, “The matter is with us,” then it is what the people did with them in Medina. Another terminology for Malik was that he did not differentiate between modes of modernization.